A Derivative-Free Mesh Optimization Algorithm for Mesh Quality Improvement and Untangling. (31st March 2015) - Kim, Jibum; Shin, Myeonggyu; Kang, Woochul
Abstract : We propose a derivative-free mesh optimization algorithm, which focuses on improving the worst element quality on the mesh. The mesh optimization problem is formulated as a min-max problem and solved by using a downhill simplex (amoeba) method, which computes only a function value without needing a derivative of Hessian of the objective function. Numerical results show that the proposed mesh optimization algorithm outperforms the existing mesh optimization algorithm in terms of improving the worst element quality and eliminating inverted elements on the mesh.